(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
Review of Dubois, Laurent. (2005). Avengers of the New World: The Story of the Haitian Revolution. Cambridge, MA: Harvard University Press. ISBN: 0-674-01826-5.